Mistakes in the ultrasound diagnostics of the abdominal cavity in pediatrics - Agnieszka Brodzisz (Journal of Ultrasonography, 2017)
The diagnostics of the abdominal cavity in children, especially in the neonatal-infantile period, requires knowledge in the field of anatomical and physiopathological differences as well as clinical symptomatology and pathology at every stage of the child’s development. Errors and mistakes in ultrasound diagnostics of the abdominal cavity in children result from many factors, including lack of experience in examining children and the knowledge concerning most frequent ailments and pathologies as well as the incidence or no changes in the ultrasound image of the abdominal cavity organs. The assessment of the ultrasound image should be always based on clinical data of the patient, information on the past diseases, surgeries and the results of additional examinations and laboratory tests. Particular attention should be paid to the occurrence of congenital diseases and inflammations, which may have varied clinical manifestation – especially in the case of pediatric diagnostics. The variety and non-specific nature of clinical symptoms may also mask the developing neoplastic process. Mistakes in ultrasound diagnostics, especially among the youngest children, may also be caused by technical difficulties related to carrying out the examination. The above situation results from lack of cooperation with the child, who is uneasy, wailing, fails to perform orders, which may lead to overlooking the existing lesion or overinterpreting, e.g. a full stomach or residual stool in the intestines to be a pathology. It is also of high importance to have a good class of the ultrasound equipment and technical knowledge concerning its operation. When performing an ultrasound examination in children, it is necessary to apply a wide range of phased-array, convex and linear heads and appropriate applications, the so-called pediatric software (stomach, kidneys, true pelvis, organs at the surface).